Adipose-derived mesenchymal stem cells from patients with atherosclerotic renovascular disease have increased DNA damage and reduced angiogenesis that can be modified by hypoxia. Issue 1 (December 2016) - Saad, Ahmed; Zhu, Xiang-Yang; Herrmann, Sandra; Hickson, LaTonya; Tang, Hui; Dietz, Allan; van Wijnen, Andre; Lerman, Lilach; Textor, Stephen
Abstract Background Adipose-derived MSC (AMSCs) possess angiogenic and immunomodulatory properties that may modulate kidney regeneration. Whether these properties are retained in older patients with atherosclerotic vascular disease is poorly understood. Hypoxic conditions are known to modify properties and growth characteristics of AMSCs. We tested the hypothesis that AMSCs from older patients with atherosclerotic renovascular disease (RVD) differ from normal kidney donors, and whether hypoxia changes their functional and molecular properties to promote angiogenesis. Methods AMSCs from 11 patients with RVD (mean age =74.5 years) and 10 healthy kidney donors (mean age = 51.2 years) were cultured under normoxia (20 % O2 ) and hypoxia (1 % O2 ) for 3–4 days until they reached 80 % confluency. We analyzed expression of genes and microRNAs using RNA sequencing and real-time quantitative rt-PCR. Protein expression of selected angiogenic factors (VEGF, IGF, HGF and EGF) were quantified in conditioned media using ELISAs. Apoptosis was tested using Annexin IV staining. Results Normoxic AMSC from RVD patients grew normally, but exhibited increased DNA damage and reduced migration. VEGF protein secretion was significantly lower in the RVD AMSCs (0.08 vs 2.4 ng/mL/ cell, p <0.05) while HGF was higher. Both trends were reversed during growth under hypoxic conditions. Hypoxia upregulated pro-angiogenic mRNAs expression in AMSCs (VEGF, FGF, STC and ANGPTL4), and downregulated expression of many miRNAs (e.g., miR-15a, miR-16, miR-93, miR-424, 126, 132, 221) except miR-210. Conclusions Thus, although AMSC from patients with RVD had increased DNA damage and reduced migration, hypoxia stimulated pro-angiogenic responses via increased expression of angiogenic genes, VEGF secretion and induction of the hypoxia-inducible miR-210, while downregulating angiogenesis-related miRNAs.